Determination of the remediation effectiveness of soils accidentally contaminated by sulphuric acid by geophysical methods Determinación de la efectividad de la remediación de suelos accidentalmente contaminados con ácido sulfúrico mediante métodos geofísicos - Coria, Ignacio D. (2011)
This work demonstrates that the diagnosis of soils that have been contaminated with dangerous substances after remediation can be done with non invasive techniques, with cost and time reduction, and avoiding the sample cross contamination risks of invasive methods. The noninvasive methods used in this particular case of accidental contamination with concentrated sulphuric acid were electromagnetic induction and geoelectric. According to the results, it is concluded that the complementary use of both methods allows making a correct diagnosis of the remediation effectiveness.